ANTUN BARAC ABOUT CROATIAN LANGUAGE IN 19TH CENTURY - Marko Samardžija (Fluminensia: Journal for Philological Research, 1995)
Antun Barac (1894-1955), Croatian historian of literature, published several articles about Croatian language in the 19th century. The articles were published between 1938 and 1954. This article represents Antun Barac's attitude to some questions of the origin and development of Croatian standard language.